Emerging pharmaceutically active drugs: synthesis and pharmacology of Schiff base ligands with their metal complexes - Ekhlass Uddin; Md. Nazmul Sardar; Md. Shahin Reza; Md. Sohag Hasan; Md. Tanvir Talukder; Md. Mahbubul Hoque; Prodip Paul; Mst. Shabana Khatun; Md. Faruk Hossen; Md. Ali Asraf; Md. Kudrat-E-Zahan (Discover Chemistry)
Abstract Schiff bases (SBs) are biologically favored platforms with outstanding pharmaceutical importance due to fabrication of ligands and stable metal complexes in both organic and inorganic chemistry. These compounds have depicted anticancer, antitumor, antiviral, DNA binding, antioxidant, antibacterial, antifungal, and many more features. This article mainly focuses on synthesis reactions with emphasis on the preparation and efficacy values of the synthesized SB ligands and metal compounds which will help to discover new suitable SB compounds for future perspectives. Both gram-positive (S. aureus, S. pyogenes, B. anthracis, and so forth) and gram-negative (E. coli, P. aeruginosa, S. typhi, and so forth) bacteria have been shown to be susceptible to antibacterial activity. Several metal complexes have been shown to have antifungal properties against A. niger, C. albicans, A. flavus, and other fungal species. The least inhibitory concentration (IC50) for HIV, RSV, HSV, and coronavirus has been used to summarize the in vitro antiviral characteristics. Furthermore, cytotoxic effects against a number of cell lines, such as PC-3, HeLa, HepG-2, MCF-7, HEK-293, and HCT-116, have been studied. Besides, this paper resumes recent developments on SB metal substances appended special prior with Hg, Cr, Mn, Fe, Co, Ni, Cu, V, Cd, Zn, Pb, Pt, and Pd metals, focusing mostly on their inhibitory effects. This work will help scientists to quest advanced pharmacological SB active molecules, gaining inspiration from the versatile families of aldehydes and ketones. Graphical abstract